Pengaruh Penerapan Pembelajaran Kooperatif Tipe Pair Checks Terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP Pertiwi 2 Padang - Windi Maiendra; Hafizah Delyana; Lucky Heriyanti Jufri (STKIP PGRI Sumatera Barat, 2021)
The background of this research is that srudents’ mathematics learning outcomes are still low, students participate less and have not maximized their role in group learning. The purpose of the study was to determine the improvement of students’ mathematics learning outcomes by applying the pair checks type cooperative learning model to the VIII grade students of SMP Pertiwi 2. This type of researchis pre-experimental design research with research design one shoot case study. The population in this study were students class VIII SMP Pertiwi 2 Padang which consists of 2 classes retrieval technique. The sample was taken using purposive sampling, so that class VIII.1 was chosen SMP Pertiwi 2 Padang as a sample. The research instrument is the final test in the form of essays and reliability of questions = 0,86 with reliable criteria. Based on the calculation results, it was obtained that the percentage of learning outcomes obtained by students while using the pair checks type of cooperative learning model obtained t count = -2,5 = 2,5 (absolute value) and t table = 1,79 with the degree of truth (dk) = n-1, n = 12 then (dk) = 11 and a significant rate of 5% = 0,05. So is rejected because t count > t table. So it can be concluded that there is an increase in student learning outcomes by applying the pair checks cooperative learning model to class VIII students SMP Pertiwi 2 Padang.